Parenting experiences of formerly abducted young mothers in post-conflict Northern Uganda - Paoletti, Sara (2017)
Parenting is a universal responsibility worldwide and the basis for better future generations. In other words, the future is in parents' hands; the way the next generation is going to be largely depends on how parents experience parenting. The phenomenon of child soldiers remains prominent in more than 86 different countries. Northern Uganda has seen the brutal involvement of child soldiers during the decades-long civil war between the rebellious Lord’s Resistance Army (LRA) and the Uganda People’s Defense Forces (UPDF). It was estimated that 30% to 40% of child soldiers in Uganda were girls and most of them were compelled into forced marriages with LRA commanders. In the last decade, with the conflict on the wane, more and more Former Child Soldiers (FCS) have returned to their villages: female FCS returned with children resulted of forced sexual relationships, explaining the reason why they are called Formerly Abducted Young Mothers (FAYM). The aim of the study was to examine FAYM's parenting experiences ranging from the time they were captive (in the bush) to the time of resettlement and reintegration in their former communities. In particular, the study focuses on three specific issues: 1) parenting practices among FAYM; 2) challenges FAYM experienced and 3) support, which FAYM received towards their parenting. FAYM constituted the main participants in the study. The other participants in the study were NGOs staff. Data for this study were collected using semi-structured, in-depth individual interviews and focus group discussions. The data were analysed according to a combined approach, including: Template Analysis and Narrative Analysis. The interpretation was based on Bronfenbrenner's Ecological model and the Inglehart and Welzel's Cultural Map. Various ethical considerations such as informed consent and confidentiality were adhered to while conducting this study. The results of this study were 1) from captivity to resettlement, parenting practices underwent a shift from focusing on mere survival needs to value education and life teachings; 2) FAYM found parenting more challenging and complicated once they returned to civil society; 3) formal and informal supports were present, but quite strained and scattered, moreover almost no public welfare services or programs were available targeted at well-being of FAYM, nor at their parenting.